Australian Wholesale Telecommunications Reforms - Gregory, Mark A (Journal of Telecommunications and the Digital Economy, 2018)
The Australian telecommunications market has been reshaped with the introduction of the National Broadband Network (NBN), arguably a short-term renationalisation of the fixed-access telecommunications infrastructure. The NBN rollout commenced in 2009 and is expected to be completed by 2021. The telecommunications market has evolved rapidly as the NBN has taken shape and it is anticipated that the telecommunications industry will seek a period of certainty following the NBN’s completion. This paper considers what the government of the day should do with the NBN after the NBN is built and fully operational in 2022. It discusses four options for the ownership of NBN Co beyond 2022 and describes arguments for and against each option. Telecommunications provides an essential service, is central to the nation’s participation in the global digital economy, and the management of telecommunications infrastructure is a national priority.